Tunneled haemodialysis catheter-related right atrial thrombi: a case report - Khanam, Farzana; Chowdhury, Tufayel Ahmed; Ananna, Meheruba Alam; Rahim, Muhammad Abdur; Iqbal, Sarwar (BIRDEM Medical Journal, 2022)
Type of vascular access is an important determinant of morbidity and mortality in patients receiving haemodialysis. Though arterio-venous fistula is the optimum choice, yet patients often require central venous catheters for temporary use or sometimes as a breezing option. Central venous catheters may be complicated by sepsis, one of the most common and dreadful complications; intra-atrial thrombus formation is not uncommon and in many instances remain asymptomatic and hence unrecognized. Here, we report a case of intra-atrial thrombi complicating a young boy receiving haemodialysis through central venous catheter, who was managed successfully with combination of anti-coagulation, intravenous antibiotics and catheter removal. BIRDEM Med J 2022; 12(3): 223-225